Promoting the flow of investment resources into Nigeria's petroleum industry - Ojo, M. O.; Central Bank of Nigeria, Research Department; Awoseyila, A. P.; Anyanwu, C. M.; Odoko, F.O. (Abuja, Nigeria Central Bank of Nigeria, 1996)
Reviewing the investment climate and policy incentives designed for the Nigerian oil industry.
Includes bibliographical references.
ijb, 19/12/2018
Ref.
Keywords: petroluem; investment climate; Nigeria